Effect of Glutamine Synthetase Inhibition on Brain and Interorgan Ammonia Metabolism in Bile Duct Ligated Rats. Issue 3 (March 2014) - Fries, Andreas W; Dadsetan, Sherry; Keiding, Susanne; Bak, Lasse K; Schousboe, Arne; Waagepetersen, Helle S; Simonsen, Mette; Ott, Peter; Vilstrup, Hendrik; Sørensen, Michael
Ammonia has a key role in the development of hepatic encephalopathy (HE). In the brain, glutamine synthetase (GS) rapidly converts blood-borne ammonia into glutamine which in high concentrations may cause mitochondrial dysfunction and osmolytic brain edema. In astrocyte-neuron cocultures and brains of healthy rats, inhibition of GS by methionine sulfoximine (MSO) reduced glutamine synthesis and increased alanine synthesis. Here, we investigate effects of MSO on brain and interorgan ammonia metabolism in sham and bile duct ligated (BDL) rats. Concentrations of glutamine, glutamate, alanine, and aspartate and incorporation of 15 NH4 + into these amino acids in brain, liver, muscle, kidney, and plasma were similar in sham and BDL rats treated with saline. Methionine sulfoximine reduced glutamine concentrations in liver, kidney, and plasma but not in brain and muscle; MSO reduced incorporation of 15 NH4 + into glutamine in all tissues. It did not affect alanine concentrations in any of the tissues but plasma alanine concentration increased; incorporation of 15 NH4 + into alanine was increased in brain in sham and BDL rats and in kidney in sham rats. It inhibited GS in all tissues examined but only in brain was an increased incorporation of 15 N-ammonia into alanine observed. Liver and kidney were important for metabolizing blood-borne ammonia.